Kekuatan Hukum Penggunaan Surat Jual Beli di Bawah Tangan dalam Pendaftaran Tanah di Kabupaten Padang Pariaman - Ramadhan, Geni Rilfa; Yuslim, Yuslim; Hasbi, Muhammad (UNES Law Review, 2023)
Land is basically owned and controlled by a person or together. Sometimes the land can be transferred to another person by using an underhand sale and purchase agreement, in Padang Pariaman Regency it is known as Siliah Jariah, where the buyer replaces someone's hard work on the land he previously controlled to become the property of the buyer. So that the Siliah Jariah Letter becomes the basis for land registration at the Padang Pariaman Land Office, what is examined in this thesis are: 1) What is the certainty of the legal force of using a Sale Purchase Certificate under the hand as the basis for rights in land registration in Padang Pariaman Regency? 2) How is the implementation of the registration of land rights using a sales and purchase agreement under the hand at the Land Office of the Padang Pariaman Regency? The approach method used in this study is an empirical juridical method. This research is descriptive in nature. The data used are primary data and secondary data. The data sources in this research are library research and field research. Data was collected through interviews and document studies. The data obtained was processed through editing and coding, then analyzed using qualitative analysis. Furthermore, the data is presented descriptively. Based on the results of the research, the authors conclude: 1) The private sale and purchase agreement cannot be the basis for land registration at the Padang Pariaman Land Office, because basically the land must be owned for 20 years, or land registration can be done by means of, register the land in the name of the previous owner (seller), after which the rights can be transferred to the name of the buyer. 2) The land registration system based on private sale and purchase is generally registered through a sporadic land registration system, in which cultivators collectively register their rights with the National Land Agency of Padang Pariaman Regency.